Research on Nonlinear Vibration Characteristics of Internal Beveloid Gear Transmission System - Jianmin Wen; Chenqi Fu; Hong Zhang; Bindi You (Applied Sciences, 2023)
The internal beveloid gear has good scientific research value and a broad application field. However, there is a lack of research on the nonlinear vibration characteristics of internal beveloid gears. The present study establishes a nonlinear vibration model that takes into account axial vibration, gear torsional vibration, and radial support vibration. The effects of various excitation parameters on the vibration characteristics of the gear transmission system are analyzed and computed using the Runge–Kutta method. After analyzing the dynamic model of the gear pair using numerical methods, the harmonic balance method is employed to obtain the theoretical analytical solution for a single−stage gear. The obtained results are compared with the velocity and acceleration time−domain response curves obtained from the numerical method, and they show excellent agreement.